PRE-PROFESSIONAL TRAINING OF LYCE-LISTERS IN THE SYSTEM CONTINUOUS ECONOMIC EDUCATION ON THE BASIS EDUCATIONAL AND METHODOLOGICAL COMPLEX (NMC) (Pedagogy of Higher and Secondary Education, 2003)
No abstract.